A Study on Lung Cancer Chemotherapy Regimen Administration at Universitas Gadjah Mada Academic Hospital - Oktariyanto, Efel Erlambang; Yasin, Nanang Munif; Puspitasari, Ika (Academic Hospital Journal, 2024)
Background: One of the main ways to treat lung cancer is through chemotherapy regimens. Due to the complexity of lung cancer pathophysiology, the variability of chemotherapy given tends to cause drug interactions and toxicity in patients.Objective: Based on this, this study aims to determine the characteristics of lung cancer patients and identify chemotherapy administration patterns based on the NCCN therapy guidelines, identify interactions and side effects of chemotherapy that occur in patients diagnosed with lung cancer who are undergoing outpatient therapy at the Universitas Gadjah Mada Academic Hospital.Method: This research was carried out with a case-series design, namely by conducting a study using descriptive methods that provide an overview of patient characteristics, chemotherapy regimen patterns and their conformity to NCCN guidelines, potential drug-drug interactions (DDIs), and the incidence of side effects experienced by patients. Data was collected retrospectively through medical records of lung cancer patients undergoing outpatient treatment in the period April 2022 – April 2023 who met the inclusion and exclusion criteria.Result: There were a total of 27 patients in this study with patient characteristics predominantly in the elderly age range (> 60 years), 18 patients (66.7%), with exon 19 mutation NSCLC lung cancer type (n = 13; 92.6%), stage IV (n = 25 ; 92.6%), as well as non-smoking patients (n = 15 ; 55.6%). Chemotherapy regimen patterns at Gadjah Mada University Academic Hospital for lung cancer patients included afatinib (n = 14; 51.9%), gefitinib (n = 12; 44.4%), and cisplatin pemetrexed (n = 1; 3.7 %) with conformity reaching 100% in the accuracy of indications, dosage and usage information. In this study, it was identified that there were 2 Potential DDIs that occurred in 1 patient (3.7%) with respective risks, namely C and B which included cisplatin-furosemide and cisplatin-ondansetron interactions. Side effects were known to occur in almost all patients (n = 23; 85.2%) where side effects in the form of skin toxicity and diarrhoea were the two most frequently identified types of side effects with a percentage of 59.3% (n = 16). and 40.7% (n = 11).Conclusion: More than 90% of NSCLC showed exon 19 mutation. The most chemotherapy given to the patients was afatinib. There were a potential interaction between cisplatin and either furosemide or ondansetron.